2003
DOI: 10.1088/0264-9381/20/19/310
|View full text |Cite
|
Sign up to set email alerts
|

The Schr dinger wave functional and S-branes

Abstract: In this paper we will consider the minisuperspace approach to S-branes dynamics in the Schrödinger picture description. Time-evolution of vacuum wave functional for quantum field theory on S-brane is studied. Open string pair production is calculated. The analysis of density matrix for mixed states is also performed. * On leave from Masaryk University, Brno

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 60 publications
1
8
0
Order By: Relevance
“…In the completely the same way as in [44] we obtain that the density of the number of particle created with momentum k is equal to…”
Section: Minisuperspace Approximation and Schrödinger Picture Descrip...mentioning
confidence: 76%
See 3 more Smart Citations
“…In the completely the same way as in [44] we obtain that the density of the number of particle created with momentum k is equal to…”
Section: Minisuperspace Approximation and Schrödinger Picture Descrip...mentioning
confidence: 76%
“…We would like to calculate the vacuum expectation value of N(k, t) . The calculation of N(k, t) is completely the same as in case of S-brane dynamics [44] where it was shown that…”
Section: Minisuperspace Approximation and Schrödinger Picture Descrip...mentioning
confidence: 92%
See 2 more Smart Citations
“…The study of time-dependent open string tachyons [1,2,3,4,5,6,7] was very intensive in recent two years and also leads to the discovery of new dualities and reinterpretation some old ones, especially relation between two dimensional string theories and matrix models [8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,26,35].…”
Section: Introductionmentioning
confidence: 99%